Is speed of healing a good predictor of eventual healing of pyoderma gangrenosum? - Wilkes, Sally R.; Williams, Hywel C.; Ormerod, Anthony D.; Craig, Fiona E.; Greenlaw, Nicola; Norrie, John; Mitchell, Eleanor; Mason, James M.; Thomas, Kim S. (Elsevier, 2016)
Background: Pyoderma gangrenosum is a rare inflammatory skin condition. The STOPGAP studies compared treatments for pyoderma gangrenosum using a primary outcome of healing speed at 6 weeks. Objective: Using data from both studies we assessed the predictive value of three early predictors for healing at 6 months - speed of healing, Investigator Global Assessment and resolution of inflammation, recorded at 2 and 6 weeks. Methods: Logistic regression models were applied and the effectiveness of the three measures was assessed through estimating the positive (PPV) and negative predictive values (NPV) and the area under the receiver operating characteristic curve (AUC). Results: The PPV and NPV at 6 weeks were 63.5% (95% CI:52.4%, 73.7%) and 74.6% (95% CI:62.5%, 84.5%) respectively for speed of healing; 80% (95% CI:68.7%, 88.6%) and 74.2% (95% CI:64.1%, 2.7%) for IGA; and 72.1% (95% CI:59.9%, 82.3%) and 68.1% (95% CI:57.7%, 77.3%) for resolution of inflammation. Investigator Global Assessment had the best combined PPV, NPV and AUC at 2 and 6 weeks. Limitations: We were limited by data available from the STOP GAP trial and cohort study. Conclusion: Speed of healing, Investigator Global Assessment and resolution of inflammation were all shown to be good predictors of eventual healing.